Hydration Interventions Among Agricultural Workers: A Pilot Study. Issue 5 (8th May 2022) - Chicas, Roxana; Suarez, Jonathan; Elon, Lisa; Xiuhtecutli, Nezahualcoyotl; House, Madelyn C.; Berra, Liris; Sands, Jeff M.; Hertzberg, Vicki; McCauley, Linda
Abstract : Larger studies are needed to further quantify the beneficial effects of isotonic liquids on preventing AKI. Guidelines are needed for clinicians to provide information to counsel at risk patients on the consumption of electrolyte fluids. Heat protections standards for workers should include guidelines on optimum electrolyte fluid hydration. Abstract : Objective: To estimate the impact of hydration interventions on postworkday hydration status and incidence of acute kidney injury (AKI). Methods: Thirty agricultural workers were first monitored on a workday without any interventions. On the intervention workday, the same workers were randomized to one of two groups: 169 ounces (oz) (5 L) of plain water ( n = 16) or 169 oz (5L) of water with electrolytes ( n = 14). Results: No participants in the electrolyte group had an estimate glomerular filtration rate (eGFR) at the end of the workday of less than 90 mL/min/1.73 m2 or met the criteria for AKI in comparison to the water group (eGFR < 90: 15%; AKI: 23%) or the control group (eGFR < 90: 28%; AKI: 18%). Conclusion: The study showed that drinking water with electrolytes may lower the risk for development of AKI among agricultural workers.